Dampak Green Accounting Terhadap Kinerja Keuangan Perusahaan Pertambangan Indonesia - Rika Henda Safitri; Relasari Relasari; Tomi Aslagar; Umi Kalsum; Rosihan Arief HS (Politeknik Ganesha Medan, 2025)
This research aims to empirically test the influence of green accounting, environmental performance, capital structure and company size on the financial performance of coal mining companies listed on the Indonesia Stock Exchange in 2018-2022. Based on the purposive sampling method, a sample of 16 companies was produced. The data analysis technique uses multiple linear regression analysis with SPSS 26 program tools. The results of this research show that green accounting and capital structure do not have a positive influence on financial performance. Meanwhile, environmental performance and company size have a positive influence on the company's financial performance.